The Relationship of Employee's Ethnic Origin to the Maturity Level of Subordinates in Situational Leadership - Fitriani Fitriani; Dapot Pardamean Saragih; Poetri Enindah Suradinata (SOCIETAS, 2022)
The uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors otherThe uniqueness of the population in Papua is the diversity of ethnicities and religions that come from all corners of the archipelago, but can live side by side without conflict. This condition also occurs in the world of government, especially in the application of situational leadership types. This study aims to determine how much the relationship between the ethnic origin of employees and the level of maturity of subordinates in situational leadership is carried out in the Papua Provincial Government. The method used is a quantitative research method using the statistical test of Sommer's dyx relationship to validate the theory of situational leadership, namely to determine the maturity level of subordinates and the leadership style used based on the suitability of the situation meeting, as well as the additional Lambda relationship test. Respondents consist of 21 (twenty one) leaders and 130 (one hundred and thirty) subordinates spread over 7 (seven) offices in the Papua Provincial Government. The results of this study found the magnitude of the relationship +0.23 (very weak relationship) where the subordinates of each ethnic origin, were at a high level of maturity, which had a weak/small relationship in the group of ethnic origin. This indicates that the Papua Provincial Government employees already have a high level of subordinate maturity (M3-M4) by applying a situational leadership style (S3-S4) and only slightly has a relationship with the employee's ethnic origin, while a large/strong relationship comes from factors other.